TINJAUAN ATAS SISTEM AKUNTANSI PEMBAYARAN GAJI KARYAWAN PADA PT PESAKA LOKA KIRANA - Larasati Amanda Putri (2022)
The writing of this final report is to increase insight, knowledge, and application of the payroll accounting system for employees at PT. Pesaka Loka Kirana aims to increase the effectiveness of the company's accounting system. The method for retrieval of information within the company is by interview and direct observation to the company related to the accounting system for paying employee salaries. The salary payment procedure carried out at the company is by recording attendance procedures, salary making procedures, and employee salary payment procedures. The accounting recording system for paying employee salaries is by setting up a payroll account, collecting payroll reports, recording the general payroll journal, posting journals to the general ledger, and reconciling payroll payments to the general ledger. Sections related to the payment of employee salaries include human resources, finance, directors, and employees.